Upaya Literasi Dalam Meningkatkan Minat Baca di Kelas 3 SDN Cileles - Ujang Jamaludin; Sigit Setiawan; Adlin Putri Pinanggih; Chelsi Arnita; Nandia Miftahul Aphdal (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
This research was conducted to identify the obstacles and efforts made by the school in increasing students' interest in reading at SD Negeri Cileles through literacy activities. This study used qualitative research methods and involved teachers and third grade students of SD Negeri Cileles as research subjects. Data collection techniques used are interviews, observation and documentation. The results of the study show that literacy activities play an important role in increasing students' interest in reading. However, there are several obstacles in implementing literacy activities in schools. These obstacles include the lack of adequate facilities and infrastructure, the lack of a variety of methods applied, and the low self-discipline of students to familiarize themselves with literacy activities. To overcome these obstacles, the school has made several efforts. These efforts include providing counseling on literacy activities to students, improving available facilities and infrastructure, and holding activities that involve active student participation.